1999
DOI: 10.1200/jco.1999.17.10.3291
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat and Carbohydrates Are Independently Associated With Circulating Insulin-Like Growth Factor 1 and Insulin-Like Growth Factor–Binding Protein 3 Concentrations in Healthy Adults

Abstract: Serum IGF-1 and/or IGFBP-3 concentrations are associated with red meat, carbohydrate intake, and fat intake and, thus, may mediate the effect of these dietary factors on the pathogenesis of several disease states. Additional studies are needed to further quantify these associations and elucidate the underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
78
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 40 publications
10
78
6
Order By: Relevance
“…Both energy and protein are needed to restore IGF-I after fasting [11]. Our results, in a study population with adequate intake of energy and protein, are consistent with most previous cross-sectional studies, in which no association between energy and protein intake and circulating IGF-I and IGFBP-3 was observed [12][13][14][15][16][17][18][19][20]. The two largest cross-sectional studies did show a positive association between IGF-I and protein intake within the normal range [22,23], as is also found by two smaller studies [21,24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both energy and protein are needed to restore IGF-I after fasting [11]. Our results, in a study population with adequate intake of energy and protein, are consistent with most previous cross-sectional studies, in which no association between energy and protein intake and circulating IGF-I and IGFBP-3 was observed [12][13][14][15][16][17][18][19][20]. The two largest cross-sectional studies did show a positive association between IGF-I and protein intake within the normal range [22,23], as is also found by two smaller studies [21,24].…”
Section: Discussionsupporting
confidence: 92%
“…Severe energy and protein restriction was found to lower serum IGF-I levels in both animals and humans [11]. Results of cross-sectional studies investigating the relation between the normal range of energy and protein intake and serum IGF-I levels are conflicting [12][13][14][15][16][17][18][19][20], with only few studies showing a significant positive association [21][22][23][24]. Alcohol consumption can possibly increase IGF-I production by the liver [25], but has been inconsistently related to IGF-I and IGFBP-3 levels in cross-sectional studies [14,15,17,22,26].…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Carbohydrates have been directly associated to higher IGF-I levels in studies in North America and the United Kingdom, where the carbohydrate components of the diet tend to be of higher GI values, 38 -40 while inverse associations were found in a study from Greece, where carbohydrate foods, as part of the Mediterranean dietary tradition, tend to have lower GI. 41 One study found a positive association between dietary GL and IGF-I, 40 and in an intervention study of diet and exercise, IGF-1 was decreased by 20% after 11 days on a high-carbohydrate/ high-fiber diet where carbohydrates accounted for 70 -75% of calories (mostly from low-GI foods such as legumes, whole grains and fruit) compared to the common intake of 50 -55% of calories. 42 In the latter study, the serum of individuals after the intervention period (high-carbohydrate/low-GI foods) reduced the growth of prostate cancer cell lines in vitro significantly more than at baseline (low fiber-high GI diets).…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial high carbohydrate=high-GI diets increased IGF-1 levels compared to low carbohydrate diets in obese subjects (Prewitt et al, 1992). The opposite was shown in a small cross-sectional study in Greece where an independent and negative association was found between circulating IGF-1 levels and energy from carbohydrates (Kaklamani et al, 1999). The Mediterranean diet, however, is known to contain several food items with low GI values and it is possible that the dietary GL in this Greek population was lower than in a typical Western diet used in the clinical study by Prewitt et al (1992).…”
Section: Glycemic Index In Chronic Diseasementioning
confidence: 93%